Pressure production in oral vestibule during gum chewing. (4th July 2015) - Nishiura, M.; Ono, T.; Yoshinaka, M.; Fujiwara, S.; Yoshinaka, M.; Maeda, Y.
Summary: The aim of this study was to record oral vestibule pressure (OVP) by the lip and cheek contraction during gum chewing, to examine the characteristics of these pressures and coordination between the OVP and jaw movement. The subjects were eight healthy adult men (mean age of 29·3 ± 3·3 years). An experimental plate that incorporated four pressure sensors on the midline of the upper jaw (Ch. 1), upper right canine (Ch. 2), upper right first molar (Ch. 3) and upper left first molar (Ch. 4) was used for measuring OVP. The right masseter electromyogram (EMG) was recorded simultaneously. Subjects chewed gum on the right side 20 times, and eight consecutive strokes were used for the analysis of the sequential order, maximal magnitude and duration of each OVP. Onset of OVP was observed at the molar on the non‐chewing side (Ch. 4) before chewing side (Ch. 3), and offset was largely simultaneous at each site. On the chewing side (Chs. 1–3), OVP onset during the interval of EMG activity reached to the peak around the end of interval and offset in the duration of EMG activity. The maximal pressure was significantly larger at Chs. 1–3 than at Ch. 4, but no significant differences were observed in duration of pressure among each site. These results suggest that OVP is coordinated with jaw movement during gum chewing, and larger pressure is produced on the chewing side than on the non‐chewing side. Our findings are quantitative indices for the evaluation of lip and cheek function during mastication.